Building a Global Evidence Base to Guide Policy and Implementation for Group Antenatal Care in Low‐ and Middle‐Income Countries: Key Principles and Research Framework Recommendations from the Global Group Antenatal Care Collaborative. (3rd October 2020) - Grenier, Lindsay; Lori, Jody R.; Darney, Blair G.; Noguchi, Lisa Miyako; Maru, Sheela; Klima, Carrie; Lundeen, Tiffany; Walker, Dilys; Patil, Crystal L.; Suhowatsky, Stephanie; Musange, Sabine
Abstract: Evidence from high‐income countries suggests that group antenatal care, an alternative service delivery model, may be an effective strategy for improving both the provision and experience of care. Until recently, published research about group antenatal care did not represent findings from low‐ and middle‐income countries, which have health priorities, system challenges, and opportunities that are different than those in high‐income countries. Because high‐quality evidence is limited, the World Health Organization recommends group antenatal care be implemented only in the context of rigorous research. In 2016 the Global Group Antenatal Care Collaborative was formed as a platform for group antenatal care researchers working in low‐ and middle‐income countries to share experiences and shape future research to accelerate development of a robust global evidence base reflecting implementation and outcomes specific to low‐ and middle‐income countries. This article presents a brief history of the Collaborative's work to date, proposes a common definition and key principles for group antenatal care, and recommends an evaluation and reporting framework for group antenatal care research.